Arthropods discovered on refugio flowering plants in Mangifera indica plantation - WIWIN WINDRIYANTI; NONI RAHMADHINI; ITO FERNANDO; RAMADHANI MAHENDRA KUSUMA (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Windriyanti W, Rahmadhini N, Fernando I, Kusuma RM. 2023. Arthropods discovered on refugio flowering plants in Mangifera indica plantation. Biodiversitas 24: 4747-4754. The diversity of Refugio flowering plants with different ways of flowering phenology provides alternative food sources for arthropods. Insects are the largest class of arthropods, most of which are ecological services that function as natural enemies and pollinators. Insects require an energy source over a long-term period to promote a stable and healthy population. The use of flowering plants as refugia can maximize the role of insects as ecological services in agroecosystems by providing natural enemies and pollinators with a source of food and shelter. The refugia plants used in this study were sunflowers (Helianthus annuus), king’s salad (Cosmos caudatus), Peruvian zinnia (Zinnia peruviana), Tridax procumbens (Asteraceae), and Alternanthera sessilis (Amaranthaceae) with hedgerow and insectary bank planting patterns. Data collection and periodic direct observation (scan sampling) were conducted by transects. Observed parameters included species composition and population of arthropods in two different agro-systems, monoculture and polyculture. Identification results showed 8 orders, including 44 morphospecies, belonging to 25 families. Arthropod abundance in the on-season of the refugia was found in 1422 individuals. Ecological engineering is a habitat manipulation technology using refugia plants that has increased the composition and population of natural enemy insects and pollinators.